Upaya Meningkatkan Self Communication Pada Materi Aljabar Melalui Diskusi Kelompok Peserta Didik Kelas VII E di SMP Negeri 11 Kota Sukabumi Tahun Pelajaran 2020 – 2021 - mutia agustina (Postulat : Jurnal Inovasi Pendidikan Matematika, 2021)
The purpose of this study is to know the increase in self-communication in algebra material through group discussions. This study is conducted using the Google Classroom platform with algebraic material. This research is a type of Classroom Action Research (Ind:Penilian Tindakan Kelas). The subject of this research is the VII E students of SMP Negeri 11,Sukabumi,I n the academic year of 2020-2021, the total is 28 students. The research data is obtained through the results of observations by researchers and documentation of student learning outcomes in the form of quizzes to see the increase in self-communication through group discussions for the grade VII students. Data analysis is carried out descriptively with the results of the study showing that through group discussions, and it can help to improve students' self-communication in algebraic material.